Communication skills - Worth, Richard (New York : Ferguson, 2009)
'Knowing how to communicate clearly and effectively in the workplace is one of the keys to career success. Communication Skills, Third Edition focuses on the importance of solid speaking, writing, listening, and conversational skills for thriving in the workplace.'--Amazon.com.
Rev. ed. of : Communication skills / Richard Worth, 1998
Includes bibliographical references (p. [160]-164) and index
Keywords: Business communication -- Juvenile literature; Commercial correspondence -- Juvenile literature; Public speaking -- Juvenile literature; Listening -- Juvenile literature; Business communication; Commercial correspondence; Public speaking; Listening